L-arginine alters myogenic genes expression but does not affect breast muscle characteristics by in ovo feeding technique in slow-growing chickens - Lu, Panpan; Morawong, Thanidtha; Molee, Amonrat; Molee, Wittawat (Frontiers in Veterinary Science, 2022)
In ovo feeding (IOF) of nutrients is a viable method for increasing muscle mass through hyperplasia and hypertrophy. The objective of this study was to evaluate the effects of IOF of L-arginine (Arg) on breast muscle weight, muscle morphology, amino acid profile, and gene expression of muscle development in slow-growing chickens. Four hundred eighty fertilized eggs were randomly divided into two groups: the first group was the non-injected control group, and the second group was the Arg group, injected with 1% Arg (0.5 mL) into the amnion on day 18 of incubation. After hatching, 160 birds from each group were randomly divided into four replicates of 40 birds each. This experiment lasted for 63 days. The results showed that IOF of Arg did not affect (P > 0.05) breast muscle weight, muscle morphology, and mRNA expression of mammalian target of rapamycin (mTOR) signaling pathway in slow-growing chickens. However, the amino acid profile of breast muscle was altered (P < 0.05) on the day of hatching (DOH), day 21 (D21), and day 42 (D42) post-hatch, respectively. Myogenic factor 5 (Myf5) mRNA expression was upregulated (P < 0.05) on D21 post-hatch. Myogenic regulator 4 (MRF4) mRNA expression was increased (P < 0.05) on DOH. And myogenin (MyoG) was increased (P < 0.05) on DOH and D21 post-hatch, in the Arg group compared to the control group. Overall, IOF of 1% Arg improved the expression of myogenic genes but did not influence muscle morphology and BMW. These results indicate that in ovo Arg dosage (0.5 mL/egg) has no adverse effect on breast muscle development of slow-growing chickens.